Study assessment, quisses, and critical thinking skill of elementary school students (Asian Journal of Educational Technology, 2022)
The use of Quizizz that can be set based on the learning objectives to be achieved. Quizizz can be used by educators as an alternative to assess learning as effectively as possible in order to achieve the learning objectives. The purpose of this study was to determine the analysis of Quizizz-Based assessment to improve critical thinking in the fourth grade of elementary school . This research uses descriptive qualitative research on the subject of 6 educators and 30 students with data collection using a questionnaire technique to students and educators. This data analysis is data reduction, data presentation, and verification. The results of this study are fourth grade students at SDN 1 Jati Indah Tanjung Bintang still need an assessment application or assessment according to the needs of the times, namely in the form of applications that can be accessed online such as quizizz in the cognitive assessment of students and have not increased critical thinking in the learning process, then the alternative solution requires the development of quizzz-based assessments to improve critical thinking in elementary school thematic learning